2012
DOI: 10.1183/09031936.00096711
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic cell instillation after bleomycin attenuates lung injury through hepatocyte growth factor induction

Abstract: Apoptotic cell clearance by macrophages and neighbouring tissue cells induces hepatocyte growth factor (HGF) secretion. HGF plays a key role in alveolar epithelial regeneration and reconstruction after lung injury. Direct in vivo exposure to apoptotic cells enhances HGF production, resulting in attenuation of pulmonary injury.We investigated the direct effect of in vivo exposure to apoptotic cells in bleomycin-stimulated lungs (2 days old) on HGF induction. Furthermore, sequential changes of bleomycin-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
73
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 54 publications
9
73
1
Order By: Relevance
“…Evidence from the literature supports a protective role for HGF in fibrotic lung disease. Apoptotic cells have been shown to modulate bleomycin lung fibrosis through the production of HGF alone [59] or in combination with PGE 2 [60]. Notably, a recent study has identified the role for a secreted factor in MSC protection against lung fibrosis and acute lung injury using conditioned medium from amniotic membrane derived cells [61] or proinflammatory cytokineactivated MSCs [62].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from the literature supports a protective role for HGF in fibrotic lung disease. Apoptotic cells have been shown to modulate bleomycin lung fibrosis through the production of HGF alone [59] or in combination with PGE 2 [60]. Notably, a recent study has identified the role for a secreted factor in MSC protection against lung fibrosis and acute lung injury using conditioned medium from amniotic membrane derived cells [61] or proinflammatory cytokineactivated MSCs [62].…”
Section: Discussionmentioning
confidence: 99%
“…52 Conversely, instillation of apoptotic cells into the lungs of mice following bleomycin lung injury reduced infl ammatory cytokine production and lung fi brosis via hepatocyte growth factor-dependent mechanisms, resulting in increased survival. 53 This last fi nding suggests that autologous apoptotic cell therapy might be benefi cial in selected settings, if issues of timing and dosage could be defi ned. However, the complexity of that approach is illustrated by the fi nding that TNF-a reduced net apoptotic cell clearance from the lung and thereby increased lung infl ammation as cells progressed to secondary necrosis.…”
Section: Acute Lung Injurymentioning
confidence: 99%
“…Like very few other compounds this drug exerts potent anti-fibrotic effect when given during the fibrogenic phase of BLM lung [35]. Our previous studies demonstrated that anti-fibrotic effects of apoptotic cell instillation after bleomycin treatment were significant on days 14 and 21 after BLM treatment [11, 20]. In addition, anti-EMT effect of apoptotic cell instillation on primary type II alveolar epithelial cells was determined at 14 days after BLM treatment [36].…”
Section: Discussionmentioning
confidence: 99%
“…Mice were cared for and handled in accordance with the National Institute of Health (NIH) Guide for the Care and Use of Laboratory Animals. Mouse pharyngeal aspiration was used to administer the solution containing BLM (5 U/kg body weight in 30 µl) [20, 21]. Two days after BLM treatment, saline alone, or 10 × 10 6 apoptotic or viable Jurkat cells in 50 µl saline were administered intratracheally ( i.t. )…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation